Religious experience and the philosophy of subjectivity: How faith shapes perception of reality - Zdzislaw Kieliszek (Pharos Journal of Theology)
In modern philosophical and theological discourse, religious experience is increasingly seen as altering human subjectivity and perception of reality. The purpose of the study was to identify the peculiarities of the Catholic understanding of religious experience, analyse its theological and phenomenological aspects, and determine the impact of faith on worldview orientations and cognitive processes. The study was based on theological, historical, hermeneutical and conceptual analysis. The study found that Catholic theology viewed religious experience as an integral element of faith, combining the subjective dimension of spiritual experience with the objective basis of church teaching. It was not limited to inner mystical experience, but was manifested through liturgical practice, the sacraments, and personal prayer, which provided the believer with the possibility of direct contact with God. An analysis of biblical texts has shown that religious experience influenced a person’s worldview and behaviour, determining his or her future life mission. It was found that faith not only shaped a person’s moral guidelines, but also influenced cognitive processes, changing the way they perceive reality. Faith determined not only the boundaries of spiritual cognition, but also created a holistic picture of existence, in which the material and transcendent were seen as a single coherent world. It also facilitated adaptation to life’s difficulties, as it allowed the believer to understand trials as part of God’s plan and spiritual growth.